Evaluasi Kesiapan Pemerintah Daerah Dalam Penanganan Bencana Tsunami - Ferlita, Shinta; Saepudin, Eli Apud; Purwasih, Ria; Al-Fauzan, Riza Zzdan; Alawiah, IIn Nur; Ramdhani, Alika Cahya (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Assessing local government preparedness for tsunami disaster is a crucial step to evaluate the effectiveness of local government policies, strategies and capacities in dealing with tsunami threats, especially in highly vulnerable coastal areas. Tsunami disaster management requires harmonious coordination between various government agencies, communities and other stakeholders. This includes aspects of mitigation, early warning systems, evacuation processes, as well as post-disaster recovery. Therefore, the objective of this study is to assess the extent to which local governments are prepared to deal with the tsunami threat, taking into account the actions already implemented, the availability of resources, as well as the readiness of personnel and existing infrastructure. In this study, the author used a qualitative analysis method that involved interviews with local government officials, disaster management officers, as well as local communities. In addition, the author also reviewed documents and data related to preparedness strategies and training. The results of the evaluation revealed that while some areas have adequate infrastructure and early warning systems in place, challenges remain in terms of inter-authority coordination, community outreach and human resource capacity strengthening. The study recommends enhancing inter-sectoral coordination, improving communication and early warning systems, and conducting regular training for civil protection officials and communities. All of these aim to improve tsunami preparedness. It is hoped that with better preparation, the negative impacts of tsunami disasters can be minimized and the number of victims reduced.